Techniques for production and detection of 2(3)S positronium - Mariazzi, Sebastiano; Caravita, R.; Vespertini, A.; Camper, A.; Rienacker, B.; Brusa, R. S.; Antonello, M.; Belov, A.; Bonomi, G.; Caccia, M.; Castelli, F.; Cerchiari, G.; et al. (Acta physica Polonica, 2020)
In this work, we show recent measurements of 2(3)S long-lived positronium production via spontaneous decay from the 3(3)P level. The possibility to tune the velocity of the 2(3)S positronium, excited following this scheme, is presented. In the light of these results, we discuss the use of the 3(3)P -> 2(3)S transition to realize a monochromatic pulsed 2(3)S positronium beam with low angular divergence. Preliminary tests of 2(3)S beam production are presented. The possibility to overcome the natural 3(3)P -> 2(3)S branching ratio via stimulated emission, and thus increasing the intensity of the 2(3)S source, is also shown. A position-sensitive detector for a pulsed beam of positronium, with spatial resolution of approximate to 90 mu m, is finally described in view of its possible application for the spatial characterization of the 2(3)S beam.
Gesehen am 20.07.2020